Colonial Origins, Institutions and Economic Performance in the Caribbean : Guyana and Barbados - DaCosta, Michael (IMF Working Papers; Working Paper ;, 2007)
The countries that were once British colonies in the Caribbean share a common language and a colonial history of slavery, dominance of a plantation-based sugar industry, and broadly similar government and administrative traditions. Following independence in the late-1960s economic strategies and performance across the region diverged. However, by the end of the 1980s, in the face of economic collapse Guyana had abandoned its strategy of "cooperative socialism", and its economic policies converged with those generally supported by the IMF and World Bank. Despite this policy convergence and shared colonial origins, economic performance and social indicators in Guyana and Barbados have continued to diverge. The paper explores some of the origins of this divergence, and, in particular, the deep seated factors that derive from the countries' history, geography, and demographics. In Guyana, while the focus on sound macroeconomic policies and donor support has been important, the most pressing requirement for sustained progress is to strengthen domestic institutions and build consensus on the country's future direction.